PERTEMPURAN SURABAYA TAHUN 1945 DALAM PERSPEKTIF PERANG SEMESTA - Endra Kusuma; Syaiful Anwar; Helda Risman; Ruslan Arief (Jurnal Inovasi Penelitian, 2021)
The Battle of Surabaya that took place in November 1945 was a major event of the Indonesian struggle which forced the international community to open their eyes to what was really happening in Indonesia. The battle that involved people from all groups fought against allies backed by NICA whose mission was to re-establish Dutch colonialism in Indonesia after Japan's defeat in World War II. The resistance of the people of Surabaya was carried out in various ways using all resources and occurred in all corners of the city. The purpose of this study was to determine the nature of the battle in Surabaya in 1945 from the perspective of universal warfare. The theory used in this analysis is the theory of universal war strategy, nationalism and people's war. This writing uses historical research methods from literature studies with historical analysis techniques using sharpness in interpreting historical facts. The result of the research shows that the battle of Surabaya 1945 does have the nature of universal warfare, which is typical of other wars that occurred in Indonesia.